2020
DOI: 10.1016/j.carbon.2020.03.020
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of elastic and total strains during ambient and high temperature deformation of a polygranular graphite

Abstract: In situ neutron diffraction and synchrotron X-ray diffraction, combined with image correlation analysis of 2D optical and 3D X-ray tomography datasets, have been used to investigate the relationship between elastic lattice strain and total strain during deformation of Gilsocarbon (IM1-24) polygranular nuclear grade graphite. The specimens were flat-end Brazilian discs under diametral loading, such that a compressive-tensile biaxial stress state was developed in the central region. The X-ray study was at ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 74 publications
(115 reference statements)
1
3
0
Order By: Relevance
“…6. This shows the expected bi-axial deformation and compares well to previous correlation studies performed on similar specimens [28]. These particular sets of images have also been correlated using commercial DIC software (LaVision DaVis 8.40) and a comparison that verifies the performance of the demon code is presented in the supplementary materials.…”
Section: Image Registrationsupporting
confidence: 81%
See 1 more Smart Citation
“…6. This shows the expected bi-axial deformation and compares well to previous correlation studies performed on similar specimens [28]. These particular sets of images have also been correlated using commercial DIC software (LaVision DaVis 8.40) and a comparison that verifies the performance of the demon code is presented in the supplementary materials.…”
Section: Image Registrationsupporting
confidence: 81%
“…Graphite has a high neutron elastic scattering cross-section [26], a strong Bragg edge associated with its basal plane [27], making it an ideal candidate for this study. There is a lack of evidence for the mechanisms of deformation of bulk polygranular graphites such as Gilsocarbon, which exhibits a change in deformation behaviour at elevated temperatures, leading to improved toughness and tensile strength [28]. Due to its polycrystalline nature and the ABAB stacking in hexagonal graphite crystals, shear by basal dislocation glide occurs readily [29] and graphite crystals also exhibit kink band formation [30].…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic studies [18][19][20] of the phonon spectrum have been reported using Raman, infrared and neutron scattering techniques. In situ measurement [21]of elastic and total strains during ambient and high temperature deformation of a polygranular graphite has been reported. The interfacial thermal conductance between graphite and substrate copper has been tuned [22] via anisotropic elastic properties of graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in nuclear graphite has gained greater attention in recent years for the development of high-temperature gas-cooled reactors and the molten salt reactors [1][2][3] as graphite acts as both the moderator and reflector in these reactor designs. The behaviors of nuclear graphite under fast neutron irradiation such as the dimensional change and irradiation creep are critical to the safety and economy of these reactor designs.…”
Section: Introductionmentioning
confidence: 99%